The effect of offering an energy and protein supplement to grazing canchim beef cows either postpartum or both pre- and postpartum on lipid blood metabolites and folliculogenesis - Oliveira Filho, B. D.; Toniollo, Gilson Hélio [UNESP]; Oliveira, A. F. D.; Viu, M. A. O.; Ferraz, H. T.; Lopes, D. T.; Gambarini, M. L. (Elsevier B.V., 2010)
This study was designed to evaluate the effect of nutritional supplementation offered during the pre- and postpartum periods on serum cholesterol, triglycerides and total lipids of Canchim beef cows and their relationship with folliculogenesis. Thirty cows with predicted calving date between September and October, kept in pastures of Brachiaria brizantha cv. Marandu together with their calves, were randomly distributed into three experimental groups: the first received only a mineral mixture (Control Group, CG); the second group received a concentrate with 16% crude protein/kg dry matter (DM) and 3000 kcal digestible energy/kg DM offered for 45 days prepartum and 120 days postpartum (PREG); the third group received the concentrate from parturition until the 120th day postpartum (POSG). Consumption was estimated at 1% of body weight, and each cow received approximately 4.0 kg/day (fresh weight) of supplement. Blood samples were taken and an ultrasound examination of the ovaries was performed twice a week until the 60th day postpartum. The body condition score (BCS) and the weight of the cows were recorded at 15-day intervals from calving until the 60th day postpartum. Data are presented as mean +/- SEM. Mean weight and BCS at calving were, respectively, 448 +/- 54.9 kg and 6.2 +/- 0.25 (PREG); 432 +/- 71.1 kg and 5.5 +/- 0.69 (POSG); and 434 +/- 66.4 kg and 5.5 +/- 0.69 (CG). Total cholesterol (TC), triglycerides (TRIG) and total lipids (TLIP) were measured using colorimetry until the 60th day postpartum. TC averages were PREG 186 +/- 62.6 mg/dL, POSG 159 +/- 43.1 mg/dL and CG 133 +/- 35.1 mg/dL (P < 0.05). For TRIG, the means were PREG 29 +/- 11.3 mg/dL (P < 0.05), POSG 24 +/- 8.1 mg/dL and CG 26 +/- 12.1 mg/dL (P > 0.05). Serum concentrations of TLIP were PREG 588 +/- 145.6 mg/dL, POSG 512 +/- 137.6 mg/dL and CG 452 +/- 122.4 mg/dL (P < 0.05). The first dominant follicle (DF) was identified on Day 21 +/- 10.3 (PREG), 36 +/- 28.5 (POSG) and 51 +/- 32.8 (CG) after calving. The difference between PREG and CG was significant (P < 0.05). TC was positively correlated with the calving to first estrus interval (P < 0.05). Results showed that nutritional supplementation before parturition assured good body condition at calving and suggested that it was effective at increasing cholesterol availability to maintain ovarian follicle function and to favor earlier resumption of ovarian activity. (C) 2010 Published by Elsevier B.V.
Keywords: Bovine; Blood metabolites; Energy supplementation; Body condition; Ovarian status